The making of a Soviet scientist my adventures in nuclear fusion and space from Stalin to Star Wars - Sagdeev, Roal'd Z. 1932- (Wiley, 1994)
Born in 1932, he had grown up in the elite culture of the technical universities and done pioneering work on the behavior of hot plasma physics in controlled thermonuclear fusion at the beginning of the cold war, a time of fierce competition between east and west in nuclear science. From his vantage point at the pinnacle of Soviet science, he observed first-hand the inner workings of its secretive military-industrial complex